MRSA and enterobacteria of one health concern in wild animals undergoing rehabilitation (Research, Society and Development, 2021)
The presence of contaminated animals in wildlife rehabilitation centers poses a threat for both animals and humans that come into contact with them or the contaminated environment. The aim of this study was to assess the presence of Staphylococcus aureus, including methicillin-resistant S. aureus (MRSA), as well as studying the biofilm formation capacity of these isolates, Yersinia enterocolitica, Salmonella enterica and Campylobacter spp. in wild animals from a rehabilitation center. During a two-year period, feces were collected from animals that were admitted to a wildlife rehabilitation center (n=324 samples). The pathogens were isolated from 51 (15.7%) animals of different species of mammals, birds and reptiles. Forty isolates (12.3%) were identified as S. aureus, of these, 32 (9.9%) were identified as MRSA and 72.5% were able to form biofilm. Y. enterocolitica was found in five mammals (5.1%), three reptiles (21.43%) and two birds (0.94%). Salmonella and Campylobacter were isolated from one bird each (0.67% and 0.67%, respectively). A wide diversity of animal species in rehabilitation centers, including birds, mammals and reptiles, can carry MRSA and enterobacteria of one health concern and eliminate in the feces. The presence of these pathogens in the gastrointestinal tract of wild animals admitted to a wildlife rehabilitation center shows the importance of microbiological monitoring of animals at the time of their admission and reinforces the need for specific hygienic-sanitary care.